THE CROSS-GENDER ROLE OF MAESTRO DIDIK NINI THOWOK IN SHAPING AN INCLUSIVE LEARNING SPACE IN ART AS A FORM OF SELF-EXPRESSION - Rafi Fadhilah Nalendra; Amara Primananda; Khoirika Zahro Alfiyyah; Stefani Lembah Manah; Nur Arif Anandhita (AKSELERASI: Jurnal Ilmiah Nasional, 2026)
This research aims to examine the role of the cross-gender maestro as an educator in shaping an inclusive learning space in the performing arts, particularly dance. The urgency of this research lies in the importance of creating learning environments that embrace diverse identities and eliminate gender stereotypes that remain prevalent in the world of art. This transformative approach is highly relevant amidst global efforts to foster equality and inclusivity in arts education. This study employs a descriptive qualitative approach with a case study on the teaching activities at the art studio of maestro Didik Nini Thowok. Data is collected through participatory observation of cross-gender dance processes and in-depth interviews with the maestro. The data analysis technique used is thematic analysis to identify and interpret the role of cross-gender art in building an inclusive learning space. The discussion highlights how maestro Didik Nini Thowok uses dance as a medium to break down gender boundaries in Indonesian performing arts. His comedic and educational approach not only demonstrates technical expertise but also educates the public about gender equality and the flexibility of social roles. The art studio he founded creates an inclusive space that is open to all, promoting diversity in traditional arts. This initiative removes stigma and prejudice, transforming into an arts education movement that is welcoming and equitable.